1987
DOI: 10.1364/josaa.4.000391
|View full text |Cite
|
Sign up to set email alerts
|

Contrast discrimination in noise

Abstract: Even the highest contrast sensitivities that humans can achieve for the detection of targets on uniform fields fall far short of ideal values. Recent theoretical formulations have attributed departures from ideal performance to two factors--the existence of internal noise within the observer and suboptimal stimulus information sampling by the observer. It has been postulated that the contributions of these two factors can be evaluated separately by measuring contrast-detection thresholds as a function of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
212
3

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(230 citation statements)
references
References 23 publications
15
212
3
Order By: Relevance
“…This is consistent with the conclusion reached by Legge, Kersten, and Burgess (1987), based on their measurements of contrast discrimination in the presence of externally added visual noise. Legge et aI.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the conclusion reached by Legge, Kersten, and Burgess (1987), based on their measurements of contrast discrimination in the presence of externally added visual noise. Legge et aI.…”
Section: Discussionsupporting
confidence: 92%
“…One way in which psychophysical facilitation can occur is if the mask gently stimulates the detecting mechanism bringing it closer to detection threshold (Legge and Foley, 1980). However, this process is typically associated with a reduction of the slope of the psychometric function (to a Weibull ␤ ϳ1.25) (Pelli, 1985;Legge et al, 1987;Bird et al, 2002;Meese et al, 2006), whereas the psychometric functions here (not shown) were affected only modestly, if at all, by mask contrast and remained steep (typical Weibull ␤ ϳ3 or 4). We have proposed an alternative account of this facilitatory effect elsewhere Meese et al, in press).…”
Section: Experiments Ii: Cross-orientation Contrast Maskingmentioning
confidence: 80%
“…The signal amplitudes required for the grating to be visible increase with the amount of external noise. Similar to the situation with electronic amplifiers, the transition point of the two regimes reveals the magnitude of the internal noise.The external noise paradigms have been used to analyze human sensitivity and reveal observer characteristics in a wide range of auditory (Ahumada & Lovell, 1971;Bos & Deboer, 1966;Eijkman, Thijssen, & Vendrik, 1966;Hartmann & Pumplin, 1988;Humes & Jesteadt, 1989;Moore, 1975;Osman, 1971;Richards, Heller, & Green, 1991) and visual tasks (Ahumada, 1987;Ahumada & Watson, 1985;Barlow, 1956;Burgess et al, 1981;D'Zmura & Knoblauch, 1998;Gegenfurtner & Kiper, 1992;Geisler, 1989;Hay & Chesters, 1972;Legge et al, 1987;Nagaraja, 1964;Pelli, 1981Pelli, , 1990Rose, 1948;Tanner & Birdsall, 1958;Tjan, Braje, Legge, & Kersten, 1995;Van Meeteren & Barlow, 1981). One important discovery is that many observer characteristics are invariant across different perceptual tasks within a modality (Pelli & Farell, 1999).…”
mentioning
confidence: 99%